Surface modification of silicon nanowire based field effect transistors with stimuli responsive polymer brushes for biosensing applications - Klinghammer, Stephanie; Rauch, Sebastian; Pregl, Sebastian; Uhlmann, Petra; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (Micromachines, 2020)
We demonstrate the functionalization of silicon nanowire based field effect transistors (SiNW FETs) FETs with stimuli-responsive polymer brushes of poly(N-isopropylacrylamide) (PNIPAAM) and poly(acrylic acid) (PAA). Surface functionalization was confirmed by atomic force microscopy, contact angle measurements, and verified electrically using a silicon nanowire based field effect transistor sensor device. For thermo-responsive PNIPAAM, the physicochemical properties (i.e., a reversible phase transition, wettability) were induced by crossing the lower critical solution temperature (LCST) of about 32 C. Taking advantage of this property, osteosarcomic SaoS-2 cells were cultured on PNIPAAM-modified sensors at temperatures above the LCST, and completely detached by simply cooling. Next, the weak polyelectrolyte PAA, that is sensitive towards alteration of pH and ionic strength, was used to cover the silicon nanowire based device. Here, the increase of pH will cause deprotonation of the present carboxylic (COOH) groups along the chains into negatively charged COO- moieties that repel each other and cause swelling of the polymer. Our experimental results suggest that this functionalization enhances the pH sensitivity of the SiNW FETs. Specific receptor (bio-)molecules can be added to the polymer brushes by simple click chemistry so that functionality of the brush layer can be tuned optionally. We demonstrate at the proof-of concept-level that osteosarcomic Saos-2 cells can adhere to PNIPAAM-modified FETs, and cell signals could be recorded electrically. This study presents an applicable route for the modification of highly sensitive, versatile FETs that can be applied for detection of a variety of biological analytes.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bio sensing; Dual-gate; Field effect transistor; Polymer brushes; Saos-2 cells; Schottky barrier; Silicon nanowire